2022
DOI: 10.1021/acsbiomaterials.1c01095
|View full text |Cite
|
Sign up to set email alerts
|

BMP2-Mediated Silica Deposition: An Effective Strategy for Bone Mineralization

Abstract: The combined use of an osteogenic factor, such as bone morphogenetic protein 2 (BMP2), with a bone scaffold was quite functional for the reconstruction of bone defects. Although many studies using BMP2 have been done, there is still a need to develop an efficient way to apply BMP2 in the bone scaffold. Here, we reported an interesting fact that BMP2 has a silica deposition ability in the presence of silicic acid and proposed that such an ability of BMP2 can effectively immobilize and transport itself by a kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Last but not least, in addition to the structural elements in bone, some growth factors such as bone morphogenic protein-2 (BMP-2) have also been applied clinically to improve bone repair, 506–510 based on the guideline that these osteoinductive biomolecules can promote the formation of bone tissue. Transforming growth factor-beta and bone morphogenic protein signaling has fundamental roles in both embryonic skeletal development and postnatal bone homeostasis.…”
Section: Rational Designs For Bmt-inspired Synthetic Materialsmentioning
confidence: 99%
“…Last but not least, in addition to the structural elements in bone, some growth factors such as bone morphogenic protein-2 (BMP-2) have also been applied clinically to improve bone repair, 506–510 based on the guideline that these osteoinductive biomolecules can promote the formation of bone tissue. Transforming growth factor-beta and bone morphogenic protein signaling has fundamental roles in both embryonic skeletal development and postnatal bone homeostasis.…”
Section: Rational Designs For Bmt-inspired Synthetic Materialsmentioning
confidence: 99%
“…The field of biomimetic silica formation has been becoming increasingly intriguing due to its potential to utilize gentle reaction conditions, control the silica structure, and facilitate relatively simple cargo loading [ 74 ]. The advancement of bio-inspired and biomimetic silica formation has been fueled by the identification of the molecules involved in natural silica biomineralization processes like silaffin peptides and polyamines [ 35 , 75 , 76 , 77 , 78 ].…”
Section: Biomineralsmentioning
confidence: 99%
“…This biosilica, which is rich in silanol groups, enhances the binding of growth factors with positively charged heparin-binding motifs compared to HAP [ 159 ]. In addition, the BMP2 protein itself has biosilica-forming properties, leading to the development of a BMP2 delivery system through self-encapsulation via BMP2-mediated silica synthesis [ 75 , 76 ]. BMP2/silica composites have demonstrated the sustained release of BMP2 from bone grafts.…”
Section: Biominerals and Composite Materials In Regenerative Medicinementioning
confidence: 99%
“…24 Ki et al developed an effective strategy for bone mineralization by incorporating bone morphogenetic protein 2 (BMP2) into a silica matrix, serving as a stable carrier for BMP2 delivery and promoting osteogenesis at low concentrations. 25 In summary, advancing our understanding of the principles of biomineralization of shells, bones, and teeth will lead to the fabrication of newly developed biomaterials. The collected articles in this special issue do not comprehensively cover the topic of biomineralization from principles to applications, but we believe that these articles and all the presentations given at BIOMIN XVI and the biomineralization summit will inspire young researchers to gain new insights into biomineralization, explore its potential applications in life science/engineering, and solve other global issues in the near future.…”
mentioning
confidence: 99%
“…Julian et al reported a dentin replacement material, an apatite–gelatin nanocomposite, which was significantly strengthened by effective cross-linking with transglutaminase and casein, resulting in a Vickers hardness that is comparable to that of human dentin . Ki et al developed an effective strategy for bone mineralization by incorporating bone morphogenetic protein 2 (BMP2) into a silica matrix, serving as a stable carrier for BMP2 delivery and promoting osteogenesis at low concentrations …”
mentioning
confidence: 99%